Determinan Intensi Whistleblowing Internal pada OPD Kabupaten Purbalingga - Ningrum Pramudiati; Rizki Nur Aziz (Telaah Bisnis, 2021)
This research aims to examine the determinants of internal whistleblowing intention at OPD Purbalingga Regency. The determinants of internal whistleblowing intention need to be examined because Indonesia is one of the countries with a high level of fraud. This research used primary data in the form questionnaires with purposive sampling method. The sample used in this study were 27 Regional Apparatus Organizations (OPD) in Purbalingga Regency, Central Java Province. The variables examined in this study were professional commitment, ethical environment, moral intensity, and personal cost. This research used descriptive analysis and multiple linear regression analysis. The results of this study indicate that professional commitment, ethical environment, moral intensity, and personal cost have a positive and partial effect on the intention to conduct internal whistleblowing at the Regional Apparatus Organization (OPD) of Purbalingga Regency. A person with a high moral intensity tends to have a high intensity to whistleblowing. This means that morals are often an important limitation for a person to take action. A person with high moral boundaries will not like anything beyond the existing moral rules.